Interactive screenspace fragment rendering for direct illumination from area lights using gradient aware subdivision and radial basis function interpolation. (May 2017) - Koa, Ming Di; Johan, Henry; Sourin, Alexei
Highlights: A deferred multi resolution rendering for direct illumination from area lights. A sub-fragment visibility test detects discontinuity within a fragment. A fragment is subdivided by analyzing its gradient of visibility discontinuities. Fragments are upsampled using Radial Basis Functions to interpolate scattered data. Our method generates fewer fragments as well as renders better and faster. Graphical abstract: Abstract: Interactive rendering of direct illumination from area lights in virtual worlds has always proven to be challenging. In this paper, we propose a deferred multi-resolution approach for rendering direct illumination from area lights. Our approach subdivides the screenspace into multi-resolution 2D-fragments in which higher resolution fragments are generated and placed in regions with geometric, depth and visibility-to-light discontinuities. Compared to former techniques that use inter-fragment binary visibility test, our intra-fragment technique is able to detect shadow more efficiently while using fewer fragments. We also make use of gradient information across our binary visibility tests to further allocate higher resolution fragments to regions with larger visibility discontinuities. Our technique utilizes the stream-compaction feature of the transform feedback shader (TFS) in the graphics shading pipeline to filter out fragments in multiple streams for soft shadow refinement. The bindless texture extension in graphics pipeline allows us to easily process all these generated fragments in an unsorted manner. A single pass screenspace irradiance upsampling scheme which uses radial basis functions (RBF) with an adaptive variance scaling factor is proposed for interpolating the generated fragments. This reduces artifacts caused by large fragments and it also requires fewer fragments to produce reasonable results. Our technique does not require precomputations and is able to render diffuse materials at interactive rates.